Endocrine biomarkers : clinicians and clinical chemists in partnership - Sadrzadeh, S. M. Hossein, 1952-; Kline, Gregory, 1971- (Clinical aspects and laboratory determination of biomarkers series, 2017)
Endocrine Biomarkers: Clinical Aspects and Laboratory Determination covers all the pre-analytical variables that can affect test results, both in the clinic and laboratory. Biomarkers of endocrine and bone diseases are discussed from both clinical and laboratory perspectives, and the authors elaborate on the teamwork-based app+roach between the clinician and the laboratory professional in the diagnosis and management of endocrine and bone disorders. Discussions include test utilization, laboratory measurement methods, harmonization and standardization, interpretation of results, and reference intervals. Each chapter ends with a discussion of one or two relevant cases with shared opinions from both a clinician and a clinical chemist. Each chapter also includes a summary box outlining key points and common pitfalls in the use of specific disease biomarkers and tests.